Is sustainable intensification possible? Evidence from Ethiopia - Mutyasira, Vine; Hoag, Dana; Pendell, Dustin L.; Manning, Dale T. (MDPI, 2018)
This paper explores the sustainable intensification possibilities facing smallholder farmers in Ethiopia. We examine the internal consistency of jointly achieving “sustainable” “intensification” by exploring the factors that lead to complementarity or tradeoffs in the outcomes. A cross-sectional survey of farms was examined in multiple regions of Ethiopia’s Highlands. The results show that some farmers can achieve both sustainability and intensification, while many do not, or cannot achieve both at the same time. We found that some actions have a common impact on both sustainability and intensification, while other factors only affect one outcome. Access to agricultural loans and farm mechanization significantly increases the likelihood of succeeding in sustainable intensification. Access to land will be critical for agricultural sustainability while access to farming information and technical services will drive agricultural intensification. Overall, opportunities to improve both sustainability and intensification are weak, but the opportunity to improve one without sacrificing the other are realistic. The results contribute to the ongoing debate on sustainable intensification and help policy makers explore alternatives for managing different intensification and sustainability scenarios to achieve agricultural development goals.